Primary hyperparathyroidism associated with hypocalcemia in a patient presenting with kidney disease - Sulková, Sylvie; Horáček, Jiří; Živný, Pavel; Řehořková, Pavla; Podhola, Miroslav; Kadlec, Mirko; Povýšil, Ctibor (International urology and nephrology, 2010)
Elevated serum parathyroid hormone (PTH) level together with hypocalcemia in chronic kidney disease usually suggests secondary hyperparathyroidism. However, primary hyperparathyroidism should also be considered, especially if concomitant vitamin D deficiency is suspected. We report a case of parathyroid adenoma associated with hypocalcemia and metabolic bone disease in a patient presenting with kidney disorder. The patient was successfully treated by parathyroidectomy that was preceded and followed by intensive calcium and vitamin D supplementation.
Keywords: Kidney Diseases; senioři nad 80 let; Humans; Female; Hypocalcemia; nemoci ledvin; paratyreoidektomie; lidé; adenom; ženské pohlaví; hypokalcemie; Vitamin D Deficiency; nedostatek vitaminu D; Aged, 80 and over; Hyperparathyroidism, Primary; Parathyroidectomy; Parathyroid Neoplasms; nádory příštítného tělíska; primární hyperparatyreóza; Adenoma